Development of Resource Sharing Services at Helsinki University Library - Juha Leppämäki (16321485) (2023)
This presentation was given by   Juha Leppämäki and Elina Kähö, University of Helsinki   Background: In 2019 the ILL services at Helsinki University Library were spread across many systems: web forms, a ticket management system, an in-house ILL software and Voyager. The systems were not communicating with each other. Information was copied manually between them. Patrons could not see interlibrary loans in the library system. Invoices were created manually.  Helsinki University Library migrated from Voyager to Ex Libris Alma in 2020. Testing Alma resource sharing started the same year. The aim was to find out if we could replace the various ILL components with Alma. Initial results were promising, and we started a development project to implement Alma’s resource sharing functions in 2021. Implementation: We set up a resource sharing library in Alma that serves all our libraries on different campuses.  Alma user records for libraries as well as records from in-house ILL system were converted into resource sharing partner records using Alma API.  ILL request forms were replaced with two new forms. The Primo resource sharing form is used for borrowing requests. For lending requests, we created a form for libraries. The form uses Alma API to send lending requests directly to Alma. Bilingual resource sharing letters (Finnish and English) were configured for email communication in Alma. Alma Analytics is used for reporting and collecting statistics. We are working to create invoices automatically based on the reports from Alma analytics.  Results:  Patrons can now make ILL requests directly from the discovery system and manage their requests by logging in. For ILL staff there is less of copying information between systems. In conclusion we succeeded in bringing the entire ILL workflow under one system, Alma.  Future: Future prospects include moving from email protocol to ISO protocol, user-oriented requests from the National Repository Library, linking document delivery services to Alma resource sharing.